An Analysis on The Socio-Economic and Demographic Factors That Have an Effect on The Risk Taking Preferences of Personal Investors - GUMUS, Fatih Burak; DAYIOGLU, Yusuf (International Journal of Economics and Financial Issues, 2014)
Individual investors make portfolio investments along with various alternatives for the purpose of increasing their profit. Most of the time, these investments carry different risk levels and investors make portfolio investments by evaluating these risks of different levels. During risky investment decisions such as portfolio selection and diversification, individual investors make their decisions under the influence of various factors. Among these; there are demographic, social and economic factors like income level, age, gender, educational background, marital status and quantity and quality level of one’s profession. This study is conducted for the purpose of examining the demographic, social and economic factors mentioned above that may have an effect on predispositions of individual investors operating in Borsa Istanbul (BIST) towards risk taking. In the analyses done within this scope, it has been demonstrated that the factors discussed above except marital status all have significant effect on the risk perception of individual investors during their portfolio investments. Keywords: Risk perception; Individual investors; Socio-Economic and Demographic Factors JEL Classifications: D81; G17; G32